How Do Absorbable Sutures Absorb? A Prospective Double-Blind Randomized Clinical Study of Tissue Reaction to Polyglactin 910 Sutures in Human Skin. (December 2014) - Cartmill, Barry T.; Parham, David M.; Strike, Paul W.; Griffiths, Liz; Parkin, Ben
Abstract Objective: To compare the tissue reaction produced by 2 gauges of implanted polyglactin 910(Vicryl) suture material in human skin. Methods: A prospective, double masked, parallel randomized IRB approved clinical trial. Consecutive patients with involutional entropion and horizontal eyelid laxity were randomly allocated to 5/0 or 7/0 gauge test suture groups. Symptoms were alleviated during the wait for definitive surgery by placement of eyelid everting sutures. After 28 days, surgical entropion correction including eyelid wedge excision was achieved. Histological analysis was carried out, masked to the suture gauge used, on the excised eyelid containing one of the temporary everting sutures. Both patient and analyst were masked to the suture group. The four primary outcome measurements were granuloma outer diameter, central cellular diameter, giant cell number and area of fibrous coat and a statistical comparison made between suture gauge groups. Results: 21 patients were allocated to each group, and histological analysis was possible in 36 patients. Significant suture-related granulomatous inflammatory reactions were found in all specimens. Medians of the measurements for 5/0 and 7/0 gauge sutures, respectively, were 0.855 mm versus 0.387 mm granuloma outer diameter (p = 0.0001); 0.464 mm versus 0.250 mm central cellular element diameter (p = 0.0003); 0.194 mm2 versus 0.053 mm2 fibrous coat area (p = 0.0009) and 0.8 versus 1.2 giant cell number (p = 0.7511). Conclusions: Polyglycolic acid sutures elicit a significant foreign body inflammatory response proportional to suture gauge. This reaction may be minimized by early suture removal. The study validates a novel and ethical approach to the examination of human skin response to implanted suture material.